STRATEGIC INTRAPRENEURSHIP PRACTICE AND BANKS INNOVATION IN SELECTED BANKS IN NIGERIA: AN EMPIRICAL ANALYSIS - Ighiebemhe, Otsupius Anthonia; Awua-Ikhia, Otsu Pius (International Journal For Research In Business, Management And Accounting, 2019)
Strategic intrapreneurship is an emerging concept and to a large extent can be adopted as a determinant of business development in Nigerian Commercial Banks. It is a concept with a high attraction due to its beneficial effect on revitalization and performance of firms. However, the concept has recorded high failure rate and the global picture of the relative contribution of intrapreneurship (cooperate entrepreneurship) has not been documented or subjected to any rigorous research efforts in literature, especially in Africa. Therefore, this study examined the relationship between Strategic intrapreneurship and bank innovation in commercial banks Nigeria. The study utilized descriptive survey design. The study population consisted of 1,419 been the employees at the headquarters of the selected six commercial banks as at January, 2016 . The Cochran formula was used to arrive at a sample size of 549 being heads of strategic units and the staff of the various units. The non-probability sampling technique using snowballing or chain sampling technique was adopted. The instrument used for the study was a questionnaire titled: Strategic Intrapreneurship and Business Development Questionnaire (SIBDQ) with 82 % response rate. The instrument was validated and the Cronbach Alpha reliability for construct ranges between 0.733 and 0.91. The data collected were analyzed using the descriptive statistics and correlation coefficient was used to test hypotheses. Findings revealed that there is a strong positive and significant relationship between strategic intrapreneurship practice and banks innovation in Nigeria (r=.633, p = 0.000<0.05). There is a moderate linear relationship between intrapreneurship practice and innovation (r=.441, p = 0.000<0.05). In conclusion, strategic intrapreneurship positively influenced business development of commercial banks in Nigeria. The study therefore, recommended that bank operators in Nigeria should embrace strategic intrapreneurship as a concept, tool to be used and as a practice in their operations to be able to achieve sustainable business development.